DOI: 10.3990/1.9789077172384
|View full text |Cite
|
Sign up to set email alerts
|

Virtual tool reworking: New strategies in die design using finite element forming simulations

Abstract: Computer-aided engineering (CAE) has significantly expedited product development in the automotive industry. In the process design and planning of deep drawing processes, computer-aided design tools and finite element (FE) simulations are used together in order to achieve a high-quality product within an acceptable time-span. Here, finding the right shape for the forming tools is one of the most important tasks. However, when the tools are manufactured and tested on the prototype press the quality of the proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…The iterative spotting steps performed during the die try-out aim to homogenize the contact pressure within the die, to compensate for the fact that the elastic deformation is unknown [1]. Different methods for analysis and virtual rework of tool structures and surfaces, including the combination of structural behaviour with sheet metal forming simulations are described in [2]. The results show that the elastic deformation of the tools changes the blank draw-in significantly, leading to considerable changes in the product's quality measures [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The iterative spotting steps performed during the die try-out aim to homogenize the contact pressure within the die, to compensate for the fact that the elastic deformation is unknown [1]. Different methods for analysis and virtual rework of tool structures and surfaces, including the combination of structural behaviour with sheet metal forming simulations are described in [2]. The results show that the elastic deformation of the tools changes the blank draw-in significantly, leading to considerable changes in the product's quality measures [2].…”
Section: Introductionmentioning
confidence: 99%
“…Different methods for analysis and virtual rework of tool structures and surfaces, including the combination of structural behaviour with sheet metal forming simulations are described in [2]. The results show that the elastic deformation of the tools changes the blank draw-in significantly, leading to considerable changes in the product's quality measures [2]. Nevertheless, many of the methods suggested to combine the structural analysis and forming simulation into one FE-model lead to large models, which are time-consuming to solve when scaled to industrial dies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research and experience points to many advantages if sheet metal forming is simulated with elastic dies [1][2][3][4][5][6][7][8]. Some areas that are enabled by simulations with elastic dies are virtual spotting, improved digital twins, and improved production support.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason is the lack of die CAD models before the later stages of stamping projects. Previous research during the last couple of decades indicated large benefits if elastic dies and presses are included in SMF simulations [1][2][3][4][5][6][7][8]. The benefits of simulations with elastic tools are also seen in related manufacturing techniques using dies and presses.…”
Section: Introductionmentioning
confidence: 99%